1999
DOI: 10.1021/jp991590u
|View full text |Cite
|
Sign up to set email alerts
|

A Model Study of CO−CO Adsorbate Interaction on Si(100)-2×1

Abstract: The CO-CO adsorbate interaction on Si(100)-2×1 has been investigated with ab initio molecular orbital and hybrid density functional theory calculations using cluster models of the surface. Different adsorption combinations for one and two CO molecules on single-and double-dimer cluster models, Si 9 H 12 and Si 15 H 16 , respectively, are described. Our calculations indicate that the second CO molecule is physisorbed on the same surface Si dimer where the first CO molecule is chemisorbed. The chemisorption of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
(61 reference statements)
1
8
0
Order By: Relevance
“…Recently, we have carried out a series of quantum-chemical studies on the adsorption mechanisms of CO, , NH 3 , , HN 3 , C 2 H 2 , CH 3 OH, CH 2 O, and HCOOH 12 with the reconstructed Si(100)-2 × 1 surface using the density functional theory and the cluster models of the surface. We have also extended our theoretical study to the adsorption, isomerization, and decomposition of the HCN molecule on the Si(100)-2 × 1 surface. The preliminary result of this work using a single-dimer Si 9 H 12 surface model has been published previously .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have carried out a series of quantum-chemical studies on the adsorption mechanisms of CO, , NH 3 , , HN 3 , C 2 H 2 , CH 3 OH, CH 2 O, and HCOOH 12 with the reconstructed Si(100)-2 × 1 surface using the density functional theory and the cluster models of the surface. We have also extended our theoretical study to the adsorption, isomerization, and decomposition of the HCN molecule on the Si(100)-2 × 1 surface. The preliminary result of this work using a single-dimer Si 9 H 12 surface model has been published previously .…”
Section: Introductionmentioning
confidence: 99%
“…Early theoretical studies reported that both T-CO and B-CO were stable, , which is in contrast to a recent theoretical result that the B-CO is unstable . A model of CO–CO adsorbate interaction on the Si(001)-(2 × 1) surface was also calculated by using cluster models of the surface …”
Section: Introductionmentioning
confidence: 95%
“…8 A model of CO−CO adsorbate interaction on the Si(001)-(2 × 1) surface was also calculated by using cluster models of the surface. 9 Thus, previous studies on the CO adsorption on Si(001) suggest scattered adsorption behaviors lacking a consensus. Some reported a unique adsorption configuration, while others reported two different configurations.…”
Section: Introductionmentioning
confidence: 99%
“…The Si(001)- c (4 × 2) surface adsorbs CO molecules below ∼100 K with an adsorption probability close to unity without decomposition. , There are two stable adsorption sites, where CO either (i) terminates a dangling bond at the down-Si of a dimer (T-CO), or (ii) sits on the metastable bridge site of two Si atoms of the dimer (B-CO). On a clean surface, T-CO is the ground-state configuration, and the formation of B-CO requires an activation energy of 1.1 eV, which can be achieved, for example, by an accelerated CO molecular beam .…”
Section: Introductionmentioning
confidence: 99%